Development and Validation of an Informal Learning Experience Level Assessment Scale - Ataman Karaçöp; Tufan İnaltekin (Jurnal Penelitian dan Pembelajaran IPA, 2026)
This study aimed to develop and validate an Informal Learning Experience Level Assessment Scale (ILE-LAS) designed to assess middle and high school students’ participation in informal learning experiences that support their cognitive, intellectual, and personal development across everyday social, cultural, and material environments. The sample of the study consists of 5th to 10th-grade students studying in central, district, and village schools in a city in the northeastern region of Türkiye (1st phase: 1224 students, 2nd phase: 1312 students). This study follows a survey design. The construct validity of the ILE-LAS was assessed using Confirmatory Factor Analysis (CFA) for the factors revealed by Exploratory Factor Analysis (EFA). The results of the study show that the ILE-LAS contains a valid and reliable structure consisting of seven factors (social media usage, time spent on shopping and entertainment activities, leisure activities, technology use, hobbies, travel and interesting activities, educational, cultural, and sports activities related or unrelated to school, library and research activities, and activities requiring independent decision-making) and 25 items. As a result of this research, the ILE-LAS, which allows the identification of participation in activities that promote informal learning through interactions with other individuals or independently within social and material environments, has been made available for use within the Turkish educational and cultural context and contributes to the broader body of research on informal learning.